New oxford social studies for pakistan book 4 - Horsburgh, Nicholas (Oxford University Press Pakistan, 2010)
The "New Oxford Social Studies for Pakistan Book 5" is a textbook tailored for fifth-grade students, focusing on the social, cultural, historical, and geographical aspects of Pakistan. It covers topics such as the country$1 (Bs history, government, economy, and geography, while also introducing global concepts related to citizenship, environmental awareness, and civic responsibilities. The book is designed to develop critical thinking and awareness about Pakistan's role in the world. It includes maps, illustrations, and exercises to engage students and enhance their understanding of social studies concepts.s